Influence of Integrated Marketing Communication on Customer Loyalty Survey at CV. Fashion Ponokawan Village, Krian District, Sidoarjo Regency, East Java Province, Indonesia - Fittriya, Nurul Laili; Amalia, Rizka Rahma (Jurnal Logistik Indonesia, 2022)
This research was conducted at CV. Fashin Sidoarjo, the purpose of this research is to determine the effect of integrated marketing communication on the Fashion brand on customer loyalty. Integrated marketing communication as the independent variable (X) while customer loyalty as the dependent variable (Y). The method used in this research is quantitative using a descriptive research approach and verification using the Structural Equation Model (SEM) using Partial Least Square (PLS). The sampling technique used is non-probability sampling and purposive methods. With 91 samples as respondents taken from customers of Fashion brand products. From the results of the study, the results of integrated marketing communications have a positive and significant effect on customer loyalty by 74.1%.